PCR Detection and Analysis of the Free-Living Amoeba Naegleria in Hot Springs in Yellowstone and Grand Teton National Parks - Sheehan, Kathy B. (American Society for Microbiology, 2003)
Free-living thermotolerant amoebae pose a significant health risk to people who soak and swim in habitats suitable for their growth, such as hot springs. In this survey of 23 different hot springs in Yellowstone and Grand Teton National Parks, we used PCR with primer sets specific for Naegleria to detect three sequence types that represent species not previously described, as well as a fourth sequence type identified as the pathogen Naegleria fowleri.